2021
DOI: 10.4178/epih.e2021013
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus: footprints in the population of western India

Abstract: OBJECTIVES: Cancer is a multi-factorial disease, with various intrinsic and environmental factors contributing to its occurrence. Human papillomavirus (HPV) has been associated with the occurrence of many cancers. India severely suffers from 3 HPV-associated cancers (cervical cancer, oral cancer, and oropharyngeal cancer). Hence, the present study aimed to evaluate the HPV burden in these 3 cancers among patients from the western region of India.METHODS: DNA was isolated from samples from 400 cervical cancer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A comparison of the prevalence studies on HPV in India in development of the HNC tumour is difficult, because of different methods used in HPV detection, type of specimen used and geographical location of the study. Indian studies have reported varying HPV prevalence; these differences may be due to different detecting methodologies or demographics [ 10 – 13 ]. Our study shows a high prevalence of HPV16 for all sub-sites of HNC.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the prevalence studies on HPV in India in development of the HNC tumour is difficult, because of different methods used in HPV detection, type of specimen used and geographical location of the study. Indian studies have reported varying HPV prevalence; these differences may be due to different detecting methodologies or demographics [ 10 – 13 ]. Our study shows a high prevalence of HPV16 for all sub-sites of HNC.…”
Section: Discussionmentioning
confidence: 99%
“…A global study in 2017 attributed 22.0% (95% (confidence interval) CI: 5.0-44.0) of oropharyngeal cancer incidence in India to HPV infection [4]. However, recent studies among Indian population reported wide variations of HPV prevalence among oropharyngeal cancer cases ranging between 0.0% in south India and 44.4% in north, followed by west (26.7%) with HPV 16 and 58 as the predominant genotypes [28][29][30][31][32][33]. Reported variations in HPV prevalence among cancer cases in India are due to different detection methods, population, geographic locations and sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of the included studies. These studies vary in design, including prospective observational, [22,23] cohort, [24] and cross-sectional studies. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] These studies encompass a wide range of Indian states and zones, from the southern regions of Tamil Nadu, Hyderabad, and Kerala [23,31,34] to the northern states like Uttar Pradesh, [37] and from the eastern state of Assam [27] to the central and western states such as Maharashtra, Bhopal, and Gujarat.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%